Pemanfaatan Metode Fuzzy Logic Mamdani Dalam Menentukan Lokasi Terbaik Penjualan Coffee Shop Menggunakan Matlab - Aditya Pratama, Bayu; Valdhano Oka, Valdi; Gustiawan, M. Yoris (Jurnal Etnik: Ekonomi-Teknik, 2023)
MSME business growth today continues to increase as stated on the www.indonesia.go.id website, MSME growth in 2021 reached 61.07 percent. So that it can help increase employment. One example of MSMEs is Coffee Shop which is increasingly mushrooming in certain areas. This contains business competition in the management of the coffee shop business must be the main calculation for business actors. Determining the right location will increase attractiveness for potential customers who will come, such as the location of crowds in the area such as close to lectures, in cities that have high mobility and so on, this needs to be carefully calculated in order to determine the right sales strategy. In determining it, a decision support system is needed that will help business actors in choosing a place of sale